Antenatal determination of fetal brain activity in response to an acoustic stimulus using functional magnetic resonance imaging. - Moore, R; Vadeyar, S; Fulford, J; Tyler, D; Gribben, C; Baker, P; James, D; Gowland, P (2001)
Functional magnetic resonance imaging (fMRI) is now a well-established technique for directly identifying adult brain activity. This study builds on earlier pilot work that showed that fMRI could provide direct evidence of fetal brain cortical activation in response to an auditory stimulus. The new work presented here aims to assess the sensitivity of this technique in a larger sample group. This article includes a specific discussion of the methodology required for fetal fMRI. Sixteen pregnant subjects were scanned between 37 and 41 weeks gestation, 12 had an auditory stimulus applied to the maternal abdomen (study group) and 4 had an auditory stimulus applied to the mother's ears (control group). Two of twelve (2/12) study-group patients experienced back pain so that the experiment was abandoned; 4/12 showed significant activation (P < 0.005) in one or both of the temporal lobes; 1/12 showed significant activation in the frontal lobe. A susceptibility artifact at the interface between the maternal bowel and the fetus affected 3/12 data sets. No significant activation was found in 3/4 of the control cases, and 1/4 could not be analyzed due to a susceptibility artifact.